Analisis Kekerasan Simbolik dalam Buku Pelajaran Pendidikan Agama Islam di Sekolah Dasar - Nur Ika Fatmawati; Aninditya Sri Nugraheni; Ahmad Sholikin (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2020)
This research explains about symbolic violence in Islamic religious education books is rarely done. It also checks whether or not the books used so far contain symbolic violence, because there should be no difference in religious education between upper-class and lower-class. The formulation of the problems in this study are; how the mechanism of symbolic violence in Islamic religious education textbooks in elementary schools, and how the proportion of upper-class habitus and lower-class habitus in Islamic religious education textbooks in elementary schools. This research is a qualitative study with the type of literature study. The results showed that symbolic violence still occurred in elementary schools. The mechanism that runs is through an educational strategy by hiding the process of symbolic violence in the curriculum or what we know as the hidden curriculum. One of the media used to perpetrate violence is a textbook. In Islamic Religious Education textbooks for elementary school level), there is an element of upper-class domination over the lower class. The dominance of the upper-class over the lower-classes can be seen from the proportion of habitus presented in the textbook, the number of upper-class habitus presented through sentences and pictures illustrated is far greater than the lower-class habitus.